Quasi-model free control for the post-capture operation of a non-cooperative target - She, Yuchen; Sun, Jun; Li, Shuang; Li, Wendan; Song, Ting (Acta astronautica, 2018)
This paper investigates a quasi-model free control (QMFC) approach for the post-capture control of a non-cooperative space object. The innovation of this paper lies in the following three aspects, which correspond to the three challenges presented in the mission scenario. First, an excitation-response mapping search strategy is developed based on the linearization of the system in terms of a set of parameters, which is efficient in handling the combined spacecraft with a high coupling effect on the inertia matrix. Second, a virtual coordinate system is proposed to efficiently compute the center of mass (COM) of the combined system, which improves the COM tracking efficiency for time-varying COM positions. Third, a linear online corrector is built to reduce the control error to further improve the control accuracy, which helps control the tracking mode within the combined system's time-varying inertia matrix. Finally, simulation analyses show that the proposed control framework is able to realize combined spacecraft post-capture control in extremely unfavorable conditions with high control accuracy. •An excitation-response mapping search strategy is developed.•A virtual coordinate system is proposed to efficiently compute the center of mass.•A linear online corrector is built to reduce the control error.